LOGRANGI NATAK ON CONTEMPORARY HINDI THEATRE - Rai, Shashikant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Theatre:- It cannot be said with certainty when the theatre emerged. The word theatre has been used more in modern times but all the tendencies and sensibilities inherent in theatre are present in the scriptures as well as in the people. In its limited meaning, it has been considered synonymous with the combined form of both Rangshirsha and Rangpeetha described in the Natya Shastra.